Transforming Teachers' Work Globally: In Search of a Better Way for Schools and Their Communities (Book Review) - Linda M. Hargreaves (Journal of Research in Rural Education, 2014)
This book places teachers' work and its transformative potential, at the heart of a collection of perspectives of remarkable depth and breadth. The editors, Eija Kimonen and Raimo Nevalainen, and contributors examine teachers' work in culturally and politically diverse systems. Geographically, their "search [for] a better way" spans the northern hemisphere from Japan to Washington State, USA, and from India to the Baltic. Academically it is interdisciplinary, with substantial historical, philosophical, sociological, and political components interwoven throughout, fronted by a psychologically grounded chapter which introduces the book's social cognitive constructivist approach to learning and pedagogy.